Biologically active compounds of semi-metals - Rezanka, Tomás; Sigler, Karel (Phytochemistry, 2008)
Semi-metals (boron, silicon, arsenic and selenium) form organo-metal compounds, some of which are found in nature and affect the physiology of living organisms. They include, e.g., the boron-containing antibiotics aplasmomycin, borophycin, boromycin, and tartrolon or the silicon compounds present in "silicate" bacteria, relatives of the genus Bacillus, which release silicon from aluminosilicates through the secretion of organic acids. Arsenic is incorporated into arsenosugars and arsenobetaines by marine algae and invertebrates, and fungi and bacteria can produce volatile methylated arsenic compounds. Some prokaryotes can use arsenate as a terminal electron acceptor while others can utilize arsenite as an electron donor to generate energy. Selenium is incorporated into selenocysteine that is found in some proteins. Biomethylation of selenide produces methylselenide and dimethylselenide. Selenium analogues of amino acids, antitumor, antibacterial, antifungal, antiviral, anti-infective drugs are often used as analogues of important pharmacological sulfur compounds. Other metalloids, i.e. the rare and toxic tellurium and the radioactive short-lived astatine, have no biological significance.
Keywords: Plants; Boron Compounds; sloučeniny boru; houby; Bacteria; Animals; Arsenicals; Humans; Organoselenium Compounds; arsenikové přípravky; lidé; organoselenové sloučeniny; organické sloučeniny křemíku; zvířata; Fungi; rostliny; Organosilicon Compounds